Dimensions of Entrepreneurial Success: A Multilevel Study on Stakeholders of Micro-Enterprises - Razmus, Wiktor; Laguna, Mariola (Frontiers in Psychology, 2018)
The study provides an insight into the indicators and dimensions of entrepreneurial success as evaluated from the external stockholders’ perspective. As each firm is embedded in a network of relations with stakeholders (business partners), understanding how they evaluate entrepreneurial success is important. The initial qualitative study in the form of in-depth interviews allowed us to identify the indicators of entrepreneurial success that are identified by external stakeholders of micro-firms. In the quantitative study on 475 stakeholders of 57 micro-firms, we identified the dimensions of entrepreneurial success. Using a multilevel approach, we found six dimensions of entrepreneurial success at the individual stakeholder level and four dimensions at the firm level. The results show that stakeholders perceive entrepreneurial success in terms of many dimensions, not focusing solely on economic indicators. This knowledge may inform micro-firm management and the strategies employed by practitioners supporting entrepreneurs.